Mapping the Neuroexposome: Integrative Analysis of Dementia Risk Factors through Multi-Omics and Environmental Profiling in the Egyptian Population. - Othman, Mai Ahmed SaadZaghloul (AUC Knowledge Fountain, 2026)
Background: Dementia represents one of the most pressing public health challenges of the twenty-first century, with the global burden projected to reach 153 million cases by 2050. Egypt, as the most populous Arab nation, faces a corresponding rise in age-related diseases, yet comprehensive data from low- and middle-income countries remain severely limited. The neuroexposome framework, integrating genetic susceptibility, environmental exposures, and metabolic alterations, offers a powerful strategy to characterize the complex interplay between internal and external risk factors for Alzheimer's disease (AD) and Alzheimer's disease Related Dementias (ADRD). Objectives: This thesis aimed to: (1) examine the distribution of APOE alleles and their interaction with sex in relation to AD risk within the Egyptian population; (2) investigate associations between blood metal concentrations (arsenic, lead, mercury, and lithium) and AD risk and cognitive performance; and (3) characterize the metabolomic profiles of clinically diagnosed AD and VaD patients compared to cognitively healthy controls. Methods: A multi-center, cross-sectional observational study was conducted across six Egyptian governorates (Cairo, Mansoura, Beni Suef, Assiut, Aswan, and Sohag) through the Egyptian Dementia Network (EDN) registry. APOE genotyping was performed using Kompetitive Allele-Specific PCR (KASP). Blood metal concentrations (arsenic, lead, mercury, lithium) were quantified using inductively coupled plasma-optical emission spectrometry (ICP-OES). Untargeted metabolomics was performed using liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS). Statistical analyses included Firth's penalized logistic regression, generalized regression models, network analysis (GeneNet), and pathway enrichment analysis (MetaboAnalyst). Results: Study 1 (Genomics): The APOE ε3 allele predominated in both AD patients (83.3%) and controls (83.6%). The ε4 allele was more frequent in AD (12.7%) than controls (8.0%) (aOR = 1.09, 95% CI 0.46-2.49, p = 0.85), while ε2 was less frequent in AD (4.0%) than controls (8.5%) (aOR = 0.82, 95% CI: 0.24–2.36, p = 0.73). Neither association reached statistical significance after multiple testing correction and adjustment to age, sex, and geographical area. Sex-stratified analyses revealed no significant sex-specific effects. Study 2 (Environmental Metals): AD patients exhibited significantly higher blood concentrations of arsenic (p = 3.39×10⁻⁹) and lead (p = 0.0014) compared to controls. Lithium concentrations were lower in AD patients, with significance emerging in sensitivity analyses. Higher arsenic levels were strongly associated with increased AD risk (OR = 1.60, p < 0.001), while lithium was inversely associated with AD status (OR = 0.95, p = 0.006). Spearman correlation revealed significant negative associations between arsenic (p = -0.556), lead (p = -0.300), mercury (p = -0.306) and MMSE scores, while lithium showed a positive correlation (p = 0.309). Study 3 (Metabolomics): Fifty-nine metabolites were significantly altered in AD and 69 in VaD compared to controls. Twenty environmental and agrochemical contaminants were detected in AD patients, and 31 in VaD patients. Pathway enrichment revealed shared disruption of the TCA cycle in both conditions (AD: p = 0.0028; VaD: p = 0.0036). AD showed distinct enrichment in amino acid metabolism (BCAA biosynthesis, p = 0.0057), while VaD showed unique enrichment in purine metabolism (p = 0.0044). Nine metabolites significantly differed between AD and VaD, including 5'-methylthioadenosine (1.9-fold higher in VaD, p = 5.87×10⁻⁸) and guanosine (2-fold higher in VaD, p = 0.0009). Study 4 (Network Analysis): AD patients showed a denser metabolic network (129 edges, density = 0.0430) compared to controls (106 edges, density = 0.0362). FAD emerged as a super-hub in AD (degree increase of +7), while cystine (-4) and S-adenosyl-L-methionine (-3) lost connectivity. VaD patients also exhibited a denser network (109 edges, density = 0.0393), with hydroxybutorphanol (+6) and oleic acid (+6) as top hubs. Study 5 (APOE-Stratified Metabolomics): Six metabolites showed nominally significant alterations in ε3/ε4 carriers compared to ε3/ε3 homozygotes: oleic acid (p = 0.001), linoleic acid (p = 0.009), retinoic acid (p = 0.004), FAD (p = 0.008), cytidine (p = 0.049), and tetrahydropapaveroline (p = 0.041). Pathway enrichment revealed alterations in biosynthesis of unsaturated fatty acids (p = 0.0048) and riboflavin metabolism (p = 0.0125). Conclusion: This thesis provides the first comprehensive characterization of the neuroexposome in an Egyptian population. The findings demonstrate that: (1) APOE ε4 shows a directional trend toward increased AD risk consistent with global literature, though larger cohorts are needed for definitive conclusions; (2) elevated arsenic and lead exposure are strongly associated with AD risk and cognitive decline, while lithium shows a protective association; (3) significant elevation of 20 agrochemical contaminants in AD patients and 31 in VaD patients, including triazine herbicides (prometryn), chloroacetamide herbicide metabolites (dimethenamide ESA), sulfonylurea herbicides (foramsulfuron), and triazole fungicide metabolites (prothioconazole-desthio), suggests that environmental pesticide exposure may contribute to neurodegenerative processes through mitochondrial dysfunction, lipid metabolism disruption, and oxidative stress; (4) AD and VaD exhibit both shared (TCA cycle) and distinct (purine metabolism in VaD, amino acid metabolism in AD) metabolic signatures, with potential discriminatory biomarkers; (5) network reorganization with FAD as a central hub suggests systemic mitochondrial dysfunction; and (6) APOE ε4 carriers show distinct metabolic alterations in lipid and energy pathways, including downregulation of oleic acid, linoleic acid, and FAD. These findings identify modifiable environmental risk factors—both heavy metals and agrochemicals—provide population-specific genetic data, and demonstrate the potential of metabolomics for dementia subtyping. The establishment of the Egyptian Dementia Network creates infrastructure for future longitudinal studies in this underrepresented population.